Reference fixing and the stiffness of reference or three (would be) puzzles concerning names - Ernesto Napoli (Rivista di Estetica, 2011)
This paper deals with three puzzles concerning reference. The first concerns the Kripkean distinction between reference fixing by description and meaning giving. The second concerns the compatibility of two properties of names, arbitrariness and rigidity across world. The third concerns the tenability of the notion that a name means its bearer considering that a name is meaningful even when the bearer is no longer. The solution of the first consists in seeing that the distinction involved is not essentially a modal distinction. The solution of the second consists in setting things right with our modal talk. The solution of the third consists in realizing the persistence across times of the enjoyment of certain properties.